Analysis of effects of detonation of explosive substances on humans from characteristic curves explosive mass–distance from the origin of the explosion. Issue 3 (14th November 2015) - González Duperón, Esther; Martínez Gil, Marta; Giménez Francés, Borja; González Ferradás, Enrique
Abstract : The serious consequences of explosions justify the efforts in prevention. The inherent danger of the phenomenon and the possibility of causing other concatenated accidents (domino effect) can increase the damage. To assess the damage and plan the emergency, it is necessary to determine the possible scope of dangerous magnitudes of the explosion (high pressure, mechanical impulse, and range of the fragments). It is important to consider that the peak overpressure of explosive detonation is relatively high and impulse width short near the source. Both parameters (overpressure and impulse) decrease with the distance but the decrease is not uniform, so that the ratio of contributions of overpressure and impulse to damage of receptors differ. In this work, the TNT equivalence method has been selected to determine the overpressure and impulse of the wave when detonation of high explosives occurs outdoors and the most recognized PROBIT functions to estimate the consequences of such accidents on humans. Combining both methodologies for each type of damage, graphical relationships of the primary parameters were obtained. Previously existing relationships have been parameterized to facilitate its implementation in software and to provide intuitive information to use it in studies of risk analysis of these accidents. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 233–240, 2016